Giant Sequoia—Forest, Monument, or Park?: Political-Legal Mandates and Socio-Ecological Complexity Shaping Landscape-Level Management. Issue 6 (2nd June 2020) - Jenkins, Jeffrey; Brown, Madeline
Abstract: Giant sequoia are endemic to the western slope of the Sierra Nevada, confined to approximately seventy groves spared from 19th century timber harvests. While nearly half of these groves were afforded protections through early National Park designations, only recently at the turn of the 21st century have the remainder of these been given protections on multiple use National Forest land. However, these megaflora continue to be impacted by forces exogenous to the groves themselves, including climatic change, high severity wildfire, exurban land use pressures, and industrial levels of tourism. The history, designation and current management of Giant Sequoia National Monument is emblematic of this shift from proximate impacts to a recognition of more systemic, landscape-level phenomena. We explain this shift in the scale of management through political-legal mandates, climatic and ecological complexity, and permissible recreational activities. The landscape unifies these processes across a monument on forest land, adjoined by parks.